Current concepts on the treatment of heart failure - Pérez Araníbar, E. (1954)
In recent years some concepts have been reviewed on the treatment of Heart Failure. Of interest them known for their practical value, since the failure of the myocardium is the stage at which it inevitably comes in the course of many circulatory disorders.